Costing Study on Early Childhood Education and Development in Nepal : A Case for Investment in ECED - World Bank; UNICEF (World Bank, Washington, DC, 2020)
Skill formation and human capital accumulation are a lifetime process, and quality early childhood education and development (ECED) is critical for ensuring that children get a head start in this process. Recognizing the importance of ECED, the sustainable development goals (SDGs) include an early childhood development (ECD) target which aims to increase the percentage of children under five years of age who are developmentally on track in health, learning, and psychosocial well-being. Nepal has strived to achieve this target over the past decades, but significant disparities remain. The study provides cost estimates of improving existing and introducing new inputs to improve the quality of ECED in Nepal. The analysis shows that the cost of implementing different policy options while can be considered substantial compared to the current allocation, the increase required compared to the overall education budget is modest. A strong monitoring and evaluation (M and E) system with required data and information on the sub-sector, including data on child development outcomes, needs to be collected on a regular basis to track performance and inform future policies and reforms.